Chemical investigations into the lipid fraction of latent fingermark residue - Frick, Amanda Akiko (Curtin University, 2015)
The lipid fraction of latent fingermark residue encompasses a number of compounds crucial to fingermark detection on wetted porous substrates. This thesis describes investigations into the detection and chemical analysis of the lipid fraction of latent fingermarks. Two novel reagents for fingermark detection were developed from lipophilic histological stains. Chemical analysis of fingermark lipids found insufficient variation to discriminate between individuals or donor traits, however significant differences were observed as a function of sample age.